Analysis of Stunting Program Problems in Kalurahan Bejiharjo Kapanewon Karangmojo Gunungkidul Regency - Pujiati, Heri Roh; Lestari, Ratna Dwi (Universitas Ibn Khaldun Bogor, 2024)
The Special Region of Yogyakarta has a duty to pursue the stunting reduction target because the prevalence of stunting in DIY is still considered high. One of them is the Gunungkidul region where the stunting prevalence is still 35%. Kalurahan Bejiharjo with a total of 4890 families and a population of 16,156 people spread across 20 pedukuha. is an area that is quite close to the district center, only about 5 km from the district city center, but the number of stunting cases in Bejiharjo is high. The step taken by the government to deal with stunting is to optimize the role of posyandu. One of the roles that is considered to be able to help deal with stunting in Bejiharjo Village is the role of posyandu in providing nutrition health counseling and counseling whose aim is to increase awareness and knowledge of mothers under five so that better behavior changes occur. The purpose of this study is to analyze the role of posyandu in dealing with stunting and the factors that influence it. The method used is qualitative descriptive. Using primary data from interviews with mothers under five, posyandu cadres and Nutrition Officers of UPT Puskesmas Karangmojo also observed. Secondary data in the form of research journals, books, and related documents are obtained from literature studies. It was found that the role of posyandu in providing counseling and nutritional health counseling is more preventive. This role is considered not optimal even though the ability to deliver counseling materials by cadres has tried their best, but sometimes there are still some families who do not carry out the information conveyed even they do not fully understand by toddlers or families. Some other obstacles are such as the posyandu budget to deal with stunting which is limited and sometimes slows down, there are still unmet infrastructure facilities and the quality of posyandu cadres also still requires more intense coaching. It is recommended that the development of posyandu cadres should be carried out consistently and periodically with the focus being the delivery of counseling materials and nutrition health counseling as well as the fulfillment of infrastructure facilities and budgets for handling stunting which are still lacking or often slow to decline.